The investigation of technological conditions of pectin withdrwal from potato and study of its structure pectin - Pastukh, Hanna; Grabovska, Olena (My University, 2013)
The optimum conditions for extraction of pectin from potato pulp. Studied the physicochemical properties of potato pectin. Using infrared spectroscopy structure of potato pectin extracted using enzyme preparations and without pretreatment enzymes
Keywords: гідроліз; ІЧ-спектроскопія; пектин; картопляна мезга; гидролиз; ИК-спектроскопия; кафедра технології цукру і підготовки води; картофельная мезга; hydrolysis; IR spectroscopy; pectin; potato pulp